Study on Cerebral Venous Thrombosis From 2014 to 2023: A Bibliometric Analysis via CiteSpace - Min Li MD, PhD; Shuling Wan MD; Xuefan Yao MD; Ran Meng MD, PhD; Xunming Ji MD, PhD (Clinical and Applied Thrombosis/Hemostasis)
Objective We aimed to explore the development status, turning and key points, and emerging trends of the cerebral venous thrombosis (CVT). Methods Literature pertaining to CVT published from 2014 to 2023 in the Web of Science Core Collection database was searched. The 6.3.R1 version of CiteSpace software was used to conduct a bibliometric analysis. Results A total of 2421 articles were ultimately retained. The annual publication volume exhibited a general trend of gradual growth, culminating in 2022. In terms of both publication volume and citation frequency, the journal “Stroke” emerges as the preeminent publication with high quantity and quality. The United States, China and India have become the foremost contributors while Pakistan and England exhibit a strong international collaboration. Ferro JM from Universidade de Lisboa, Coutinho JM from University of Amsterdam and Ji XM from Capital Medical University from are identified as the leading scholars. Burst analyses of keyword and co-cited references reveal that prior to 2021, the predominant research topics in the field of CVT were epidemiology, diagnosis and management, with increased attention to endovascular therapies and novel imaging modalities. From 2021 to 2023, the focus has shifted primarily to COVID-19 and vaccine-induced immune thrombotic thrombocytopenia (VITT). Conclusion Over the past decade, research on CVT has demonstrated continuous growth. The most influential institutions and scholars were from Europe and China. Our analysis showed that core research priorities in CVT centered on epidemiology, diagnosis and management while the COVID-19 pandemic temporarily shifted focus toward COVID-19 and VITT associated CVT.